2017
DOI: 10.3390/ijerph14101100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Diarrheagenic Escherichia coli Isolated in Organic Waste Products (Cattle Fecal Matter, Manure and, Slurry) from Cattle’s Markets in Ouagadougou, Burkina Faso

Abstract: Cattle farming can promote diarrheal disease transmission through waste, effluents or cattle fecal matter. The study aims to characterize the diarrheagenic Escherichia coli (DEC) isolated from cattle feces, manure in the composting process and slurry, collected from four cattle markets in Ouagadougou. A total of 585 samples (340 cattle feces, 200 slurries and 45 manures in the composting process) were collected from the four cattle markets between May 2015 and May 2016. A multiplex Polymerase Chain Reaction (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
(55 reference statements)
2
12
0
Order By: Relevance
“…Total eight (100%) isolates showed the presence of aggR gene, followed by five (62%) est gene, five (62%) elt gene, three (37.5%) eae gene and two (25%) Asp gene, respectively. Bako et al (2017) detected est, elt and aggR genes which was in accordance to the present study. High prevalence of these genes indicated the improper management of the effluents and spread of E. coli from humans to animals through environment and vice versa.…”
Section: Resultssupporting
confidence: 93%
“…Total eight (100%) isolates showed the presence of aggR gene, followed by five (62%) est gene, five (62%) elt gene, three (37.5%) eae gene and two (25%) Asp gene, respectively. Bako et al (2017) detected est, elt and aggR genes which was in accordance to the present study. High prevalence of these genes indicated the improper management of the effluents and spread of E. coli from humans to animals through environment and vice versa.…”
Section: Resultssupporting
confidence: 93%
“…In Kenia, it was also reported as the third most frequent DEC (10%) in slaughtered goats, while an investigation in Mexico rated as the second most frequent in bovines, the same as in Burkina Faso (4%) (Njoroge et al 2013;Navarro et al 2018;Kagambéga et al 2012). Previous reports about ETEC have been described in bovines with/without diarrhea in Brazil, Vietnam (with the same number of isolates as this work), and Burkina Faso (De Moura et al 2012;Nguyen et al 2011;Bako et al 2017). There is a lack of information regarding this pathotype in slaughtered sheep in Mexico.…”
Section: Discussionsupporting
confidence: 69%
“…In Burkina, previous studies have reported the detection of ETEC in grilled chickens, cow dung and organic manure in Burkina Faso (Bako et al, 2017;Kambire et al, 2017;Somda et al, 2018). The similarity of pathovars found in human stool samples, drinking water, and in cow dung in Burkina Faso could be because the aquatic environments are contaminated with animal fecal droppings.…”
Section: Discussionmentioning
confidence: 95%